Potential Harm of Prophylactic Platelet Transfusion in Adult Dengue Patients. - Tau-Hong Lee; Joshua G X Wong; Yee-Sin Leo; Tun-Linn Thein; Ee-Ling Ng; Linda K Lee; David C Lye (Public Library of Science (PLoS), 2016)
BACKGROUND:Thrombocytopenia is a hallmark of dengue infection, and bleeding is a dreaded complication of dengue fever. Prophylactic platelet transfusion has been used to prevent bleeding in the management of dengue fever, although the evidence for its benefit is lacking. In adult dengue patients with platelet count <20,000/mm3 without bleeding, we aimed to assess if prophylactic platelet transfusion was effective in reducing clinical bleeding and other outcomes. METHOD:We conducted a retrospective non-randomised observational study of dengue patients with platelet count < 20,000/mm3 without bleeding (except petechiae) admitted to Tan Tock Seng Hospital from January 2005 to December 2008. Baseline characteristics and clinical outcomes were compared between the non-transfused vs. transfused groups. Outcomes studied were clinical bleeding, platelet increment, hospital length of stay, intensive care unit admission and death. RESULTS:Of the 788 patients included, 486 received prophylactic platelet transfusion. There was no significant difference in the presence of clinical bleeding in the two groups (18.2% in non-transfused group vs. 23.5% in transfused group; P = 0.08). Patients in the transfused group took a median of 1 day longer than the non-transfused group to increase their platelet count to 50,000/mm3 or more (3 days vs. 2 days, P <0.0001). The median duration of hospital stay in the non-transfused group was 5 days vs. 6 days in the transfused group (P< 0.0001). There was no significant difference in the proportion requiring ICU admission (non-transfused 0.66% vs. transfused 1.23%, P = 0.44) and death (non-transfused 0% vs. transfused 0.2%, P = 0.43). CONCLUSION:Platelet transfusion in absence of bleeding in adult dengue with platelet count <20,000/mm3 did not reduce bleeding or expedite platelet recovery. There was potential harm by slowing recovery of platelet count to >50,000/mm3 and increasing length of hospitalization.